Kewirausahawan Usaha Kecil Menengah (UKM) di Kabupaten Minahasa Utara - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 7 No.1, 2008 JBE UNKLAB, 2008)
This research examines the influence of six characteristics of entrepreneur and the resource management towards competitive advantages of some UKM in Kabupaten Minahasa Utara.  It finds that commitment and determination, leadership, opportunistic character, risk tolerance, creativity, independency, and adaptability could significantly influence the competitive advantages at manager level than at employee level.  Nevertheless, at manager and employee level motivation has significant effect while it is insignificant at assistant manager level.  Meanwhile, resource management is the only variable that affect the competitive advantages at all levels, i.e manager, assistant manager and employee levels.